2018
DOI: 10.1152/japplphysiol.00407.2018
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of hot water immersion on inflammation and metabolism in sedentary, overweight adults

Abstract: Regular exercise-induced acute inflammatory responses are suggested to improve the inflammatory profile and insulin sensitivity. As body temperature elevations partly mediate this response, passive heating might be a viable tool to improve the inflammatory profile. This study investigated the acute and chronic effects of hot water immersion on inflammatory and metabolic markers. Ten sedentary, overweight men [body mass index (BMI): 31.0 ± 4.2 kg/m2, mean ± SD] were immersed in water set at 39°C for 1 h (HWI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 67 publications
(90 reference statements)
6
59
3
1
Order By: Relevance
“…This is a noteworthy finding, as an increased GLP-1 response to an OGTT is predictive of chronic reductions in fasting glucose (Koopman et al 2005). The present results hence imply that the chronic reductions in blood glucose following HWI therapy (Hooper 1999;Hoekstra et al 2018) are not the result of any acute HWI-induced changes to the acute GLP-1 response. The only differential gut hormone response was observed directly following HWI, when the increase in acylated ghrelin concentration was blunted when compared with CON.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This is a noteworthy finding, as an increased GLP-1 response to an OGTT is predictive of chronic reductions in fasting glucose (Koopman et al 2005). The present results hence imply that the chronic reductions in blood glucose following HWI therapy (Hooper 1999;Hoekstra et al 2018) are not the result of any acute HWI-induced changes to the acute GLP-1 response. The only differential gut hormone response was observed directly following HWI, when the increase in acylated ghrelin concentration was blunted when compared with CON.…”
Section: Discussionsupporting
confidence: 61%
“…These chronic effects of HWI are similar to responses observed following exercise training (Kränkel et al ). HWI therapy has hence been suggested to represent a potential strategy to improve metabolic health for those unable to exercise (Hoekstra et al ), much like exercise training has been advocated to be a suitable strategy to treat and prevent diseases associated with impaired glycemic control, such as Type II Diabetes (American Diabetes Association ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human whole-body passive heating models, such as hot water immersion of >60 min whereby core body temperature is increased, higher extracellular HSP70 concentration (Faulkner et al, 2017), and intracellular HSP70 changes (Oehler et al, 2001), have been reported. The beneficial response once again is not unanimous, with others reporting chronic change (following 2 weeks of repeated therapy) in intracellular HSP70 after 45-60 min of passive heat therapy (Hoekstra et al, 2018). In a similar manner to that described for local heating, the dose of stress may be important given the lack of change in studies using 60 min heating (Hoekstra et al, 2018), in comparison to those who do report an acute increase in intracellular HSP70 following 120 min heating in 39 • C water (Oehler et al, 2001).…”
Section: Chronic Effects Of Body Warming On Heat Shock Proteinsmentioning
confidence: 95%
“…response, suggesting that the elevation of plasma IL-6 concentrations following exercise are indeed influenced by more than contraction related processes only. As hyperthermia alone can induce elevations in plasma IL-6 concentrations (Hoekstra et al 2018), the elevated circulating IL-6 concentration following the exercise bouts may therefore have also originated from other sites than the exercising muscle groups.…”
Section: R a F Tmentioning
confidence: 99%